Beka Akhalaia – A Metamodernist Georgian Poet - Kadagishvili, Dali (European Scientific Journal, ESJ, 2017)
A very intelligent and story like poetry by Beka Akhalaia amuses and saddens at the same time, but always charms its readers with its authenticity, naivety and vividness. Three verses are chosen by their likeness of composition and stylistic devices: “After January”, “There was one and there is no main Avenue” and “A dream” represents the insight of a poet, whose style of writing with symbols and enigmas, leads us into the sphere of Metamodernist poetry.